A perspective: Challenges and opportunities of a novel national dental benefit - Ness, Anna; Sihuay-Torres, Kamila; Singhal, Sonica (Frontiers in Oral Health, 2023)
In Canada, the federal government launched the interim Canada Dental Benefit (CDB) on December 1, 2022, to support access to dental care for children <12 years. The interim benefit shows government's assurance to develop a long-term national dental care program. The benefit will be a cash transfer through Canada's revenue services agency, ranging from 260 to 650 annually. This perspective examines the federal initiative and reflects on its strengths and challenges to learn lessons, which can support the long-term solution that is being currently planned. This article outlines a number of positive aspects as well as challenges from the perspectives of varied stakeholders; the feasibility of the application process; remaining potential gaps due to restricted eligibility criteria; possible effects of unrestricted oral health care services and reimbursement rates; valuing of patient autonomy; guidelines for the expansion of the program to other populations; and remaining barriers to oral health care access are analyzed. The CDB is cause for excitement for the Canadian population because it is an opportunity to reduce affordability barriers to accessing dental care. That said, it is important to discuss anticipated challenges and indirect consequences, particularly through the lens of equity, to support the new CDB and the proposed national dental care program in achieving the much-awaited goal of putting the mouth back into the body.